Coreceptor expression and T lymphocyte subset distribution in HIV-infected and TB co-infected South African patients on anti-retroviral therapy - Ngandu, Jean Pierre Kabue (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Pathology. Medical Virology))--University of Stellenbosch, 2009.